2015
DOI: 10.1007/s00464-015-4603-1
|View full text |Cite
|
Sign up to set email alerts
|

TEP versus Lichtenstein: Which technique is better for the repair of primary unilateral inguinal hernias in men?

Abstract: Introduction In the update of the guidelines of the European Hernia Society, open Lichtenstein and endoscopic techniques continue to be recommended as the surgical technique of choice for repair of unilateral primary inguinal hernias in men despite the fact that a meta-analysis had identified a higher recurrence rate for TEP compared with Lichtenstein operation. The Guidelines Group had taken that decision because one surgeon in one of the randomized controlled trials included in the meta-analysis had had a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 12 publications
4
28
0
5
Order By: Relevance
“…In this study, reporting pain last week increased the reported pain frequency by 70·8 per cent compared with pain right now. This is in line with a report of 17 000 patients from the German hernia register, evaluating pain at rest (equivalent to pain right now) and on exertion (similar to pain last week), 1 year after operation. As in the present study, IPQ was used by Westin and colleagues.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, reporting pain last week increased the reported pain frequency by 70·8 per cent compared with pain right now. This is in line with a report of 17 000 patients from the German hernia register, evaluating pain at rest (equivalent to pain right now) and on exertion (similar to pain last week), 1 year after operation. As in the present study, IPQ was used by Westin and colleagues.…”
Section: Discussionsupporting
confidence: 91%
“…However, TEP was found to have benefits in regard to postoperative complication rate (p < 0.001), pain at rest rate (p = 0.011), and pain on exertion rate (p < 0.001) [22].…”
Section: Evidence-based Selection Of Techniquesmentioning
confidence: 99%
“…In a prospectively documented registry-based study comparing 10,555 Lichtenstein repairs with 6,833 TEP repairs in primary unilateral inguinal hernias in men [22], no difference in recurrence rate, complication-related reoperation rate, and chronic pain rate requiring treatment was detected in a multivariable analysis. However, TEP was found to have benefits in regard to postoperative complication rate (p < 0.001), pain at rest rate (p = 0.011), and pain on exertion rate (p < 0.001) [22].…”
Section: Evidence-based Selection Of Techniquesmentioning
confidence: 99%
“…This fact is also confirmed by registry analysis for both TEP and the Lichtenstein repair [46]. Likewise, for ventral incisional hernias the negative influence of a high ASA score on the rate of surgical site infections was also demonstrated [47].…”
Section: Asa Scorementioning
confidence: 54%